plzzz help me out guyzz
Attachments:
![](https://hi-static.z-dn.net/files/d0e/23102cf054bb7e31c103e76412ff1de1.jpg)
Answers
Answered by
1
in Δ PQS
PS^2+QS^2=PQ^2
a^2-c^2=PS^2.....1
similarly
in Δ PRS
b^2-d^2=PS^2.....2
from 1 and 2
a^2-c^2=b^2-d^2
a^2-b^2=c^2-d^2
(a+b)(a-b)=(c+d)(c-d)
hence proved
hope this helps you
Answered by
3
hey mate
here is your answer
hope it's helpful for you
Attachments:
![](https://hi-static.z-dn.net/files/daa/917a83e1bdc13a1d4e5ef847e491074c.jpg)
Similar questions
Social Sciences,
8 months ago
English,
8 months ago
Geography,
8 months ago
Geography,
1 year ago
Social Sciences,
1 year ago
Geography,
1 year ago